1957
DOI: 10.1128/jb.73.2.199-205.1957
|View full text |Cite
|
Sign up to set email alerts
|

NUTRITION AND SPORULATION OF ALLESCHERIA BOYDII

Abstract: There have been few reports concerning the nutritional requirements of the pathogenic ascomycete, Allescheria boydii, or of its imperfect form, Monosporium apiospermum. Benham and Georg (1948) found that a strain of A. boydii isolated by Gay and Bigelow (1930) from a case of mycetoma was autotrophic for growth factors. They cultured it on a dextrose agar containing asparagine as the sole nitrogen source and observed formation of fertile perithecia. Wolf et al. (1950) conducted a detailed nutritional study of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1959
1959
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In older literature, however [24], the cleistothecial variant was much less common. Gordon [33] isolated mainly cleistothecial strains from soil, possibly corresponding to our variant 3, while strains with synnemata were rare. It may thus be supposed that variant 1 in particular, taking advantage of human natural immunodeficiency, is emerging.…”
Section: Strain I and I Ulture C O N D H N Smentioning
confidence: 88%
“…In older literature, however [24], the cleistothecial variant was much less common. Gordon [33] isolated mainly cleistothecial strains from soil, possibly corresponding to our variant 3, while strains with synnemata were rare. It may thus be supposed that variant 1 in particular, taking advantage of human natural immunodeficiency, is emerging.…”
Section: Strain I and I Ulture C O N D H N Smentioning
confidence: 88%
“…Although considerable research has been done on A. boydii, one can question the value of conclusions made from data accumulated with a single isolate. Wolf et al (38) demonstrated that a single strain of M. apiospermum was autotrophic for its vitamins, whereas Villela and Cury (37) studied a strain of A. boydii which was biotin deficient and unable to grow at 37 C. In other studies involving more than a single isolate of A. boydii or M. apiospermum (4,5,14), considerable difference has been noted among individual strains with respect to growth and sporulation. Assuming that differences might also exist in the virulence of individual isolates, the pathogenic potential of three strains of A. boydii and three strains of M. apiospermum were examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Relatively little is known about the nutrition of this organism, or about factors which influence its sporulation. Gordon (1957) reported that organic and inorganic nitrogen compounds serve equally well as a sole source of nitrogen for A. boydii, and that the organism is autotrophic for its growth factors. He also confirmed the results of Benham and Georg (1948) that rich sources of organic nitrogen stimulate the production of conidia, but inhibit the production of ascocarps.…”
mentioning
confidence: 99%